Design of Compact Vivaldi Antenna Arrays for AESA Radar System - Lekshmi, Babu Saraswathi K.; Raglend, I. Jacob (Transactions on Engineering and Computing Sciences, 2025)
This paper demonstrates a low-profile, wide band, miniaturized, Stripline fed double layered exponentially tapered slot antenna with a wide-scan capability and 10% bandwidth at the X-band frequency has been designed, fabricated, and tested. The antenna is optimized with a total size equal to 14.2x24.1x1.4 mm3 and is capable of achieving the desired bandwidth experimentally. The 9-element array and feeding network based on 1:9 T-junction power divider was employed to compose the linear array. The array elements are operating with return loss lower than 10 dB at X-band frequency. Measured results of single elements in isolated and array environment are achieved, both have a wide 3-dB beam width better than 107o in the E- and H- planes, which is capable of a linear array with wide scan angle ±55o. The linear array has a half power beamwidth of 11 degrees with side-lobe level of -12dB at 10GHz with a gain of 12dBi. These features make the antenna array fit for X-band airborne radar applications.